Febrile Seizures: Etiology, Prevalence, and Geographical Variation - DELPISHEH, Ali; VEISANI, yousef; SAYEHMIRI, Kourosh; FAYYAZI, Afshin (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Delpisheh A, Veisani Y, Sayehmiri K, Fayyazi A. Febrile Seizures: Etiology, Prevalence, and Geographical Variation. Iran J Child Neurol. 2014 Summer; 8(3):30-37. Abstract Objective Febrile seizures (FSs) are the most common neurological disorder observed in the pediatric age group. The present study provides information about epidemiological and clinical characteristics as well as risk factors associated with FS among Iranian children. Materials & Methods On the computerized literature valid databases, the FS prevalence and 95% confidence intervals were calculated using a random effects model. A metaregression analysis was introduced to explore heterogeneity between studies. Data manipulation and statistical analyses were performed using Stata10. Results The important viral or bacterial infection causes of FSs were; recent upper respiratory infection 42.3% (95% CI: 37.2%–47.4%), gastroenteritis21.5% (95% CI: 13.6%–29.4%), and otitis media infections15.2% (95% CI: 9.8%- 20.7%) respectively. The pooled prevalence rate of FS among other childhood convulsions was 47.9% (95% CI: 38.8–59.9%). The meta–regression analysis showed that the sample size does not significantly affect heterogeneity for the factor ‘prevalence FS’. Conclusions Almost half of all childhood convulsions among Iranian children are associated with Febrile seizure. References Felipe L, Siqueira M. febrile seizures: update on diagnosis and management. Siqueira LFM. 2010;56 (4):489–92. Oka E, Ishida S, Ohtsuka Y, Ohtahara S. Neuroepidemiological Study of Childhood Epilepsy by Application of International Classification of Epilepsies and Epileptic Syndromes (ILAE, 1989). Epilepsia. 1995;36 (7):658–61. Shi X, Lin Z, Ye X, Hu Y, Zheng F, Hu H. An epidemiological survey of febrile convulsions among pupils in the Wenzhou region. Zhongguo Dang Dai Er Ke Za Zhi. 2012 Feb;14 (2):128–30. Waruiru C, Appleton R. Febrile seizures: an update. Arch Dis Child. 2004;89 (8):751–6. Bettis DB, Ater SB. Febrile seizures: Emergency department diagnosis and treatment. The Journal of Emergency Medicine. 1985;2 (5):341–8. Bauchner H, Philipp B, Dashefsky B, Klein J. Prevalence of bacteriuria in febrile children. Pediatr Infect Dis J. 1987;6 (3):239–42. Lee P, Verrier Jones K. Urinary tract infection in febrile convulsions. Arch Dis Child. 1991;66 (11):1287–90. Fukuyama Y, Seki T, Ohtsuka C, Miura H, Hara M. Practical guidelines for physicians in the management of febrile seizures. Brain and Development. 1996;18 (6):479–84. Mohebbi M, Holden KR. Febrile and afebrile or provoked and unprovoked seizures? Pediatric Neurology. 2005;32 (4):291. Fallah R, Karbasi S. Recurrence of febrile seizure in Yazd, Iran. Turk J Pediatr ;52 (6):618–22. 2010 Nov–Dec;52 (6):618–22. Ghotbi N, Soleimani S. Causes of seizures in children 1 month to 12 years. Journal Of Medical Sciences Kurdistan. 2002;7 (25):32–6. Golestani M, Fallah R, Akhavan Krbasi S. Hundred cases of cerebrospinal fluid in children hospitalized due to febrile seizures. Journal of Yazd Medical Sciences 2008;16 (5):3–7. Hassanpoor H, Ghofrani M, Taheri N, Ziaee A. Risk factors in the recurrence of seizures with fever. Journal of Iran Medical Sciences 2009;16 (65):46–54. Grossman P, Niemann L, Schmidt S, Walach H. Mindfulness–based stress reduction and health benefits: A meta–analysis. Journal of Psychosomatic Research. 2004;57 (1):35–43. Ades AE, Lu G, Higgins JP. The Interpretation of Random–Effects Meta–Analysis in Decision Models. Medical Decision Making. 2005;25 (6):646–54. Ahmadian M, Javadi N. Etiologic factors and risk factors in 211 patients with seizure. Hormozgan Med J. 1996;12 (2):145–8. Amini A, Kazemi A, Ghorbani A. Causes of Seizures in Children. Iran J Neurol. 2008;7 (24):355–60. Ashrafzadeh F, hashemzadeheh A, Malek A. Febrile seizure in children six months to six years. Iranian Journal of Otorhinolaryngology. 2001;16 (1 (35)):33–9. Barzegar M, karegar maheM, KivanchehN. Epidemiologic and clinical characteristics of seizures in children with first febrile attack. Med J Tabriz Univ Med Sci. 2006;28 (1):17–21. Dehdashtian M, Momen AA, Ziae T, Moradkhani SH. Evaluation of seizure etiology in convulsive neonates admitted to Imam Khomeini and Abozar hospitals of Ahvaz 2004–2007. Jundishapur Sci Med J. 2009;8 (2):163–7. Ehsanypoor F, Khdapnahndh F, Aslani Z. The frequency of meningitis in children hospitalized with febrile seizures. Iran J Med Sci. 2004;11 (44):907–12. Fallah R, Akhavan Krbasi S, Mir–Nasseri F. Demographic and clinical characteristic children with first febrile seizure. Journal of Yazd Medical Sciences 2008;16 (5):65–1 Hosseininasab A, Daiparizzi M–H, Alidosti K. Demographic characteristics and risk factors of febrile seizure. J Med Counc IR Iran. 2006;24 (2):107–12. Kazemi A, Mousavi Nasab N, Fatemi K. Cerebrospinal fluid examination in children hospitalized. Journal Of Medical Sciences Zanjan. 2001;9 (35):32–6. Khazai T, Hossein Zadeh A, Javadzadeh M. Causes of seizures in children. Journal of Birjand Medical Sciences 2007;14 (4):45–52. Khodapanahhandeh F. Studied 107 children with febrile seizures. Journal ofIran Medical Sciences. 2001;8 (25):175–8. Moayedi AR, Nazemi Qshmy A, Safdarian F. Epidemiology and etiology of seizures and fever in children. Hormozgan M J. 2005;9 (3):153–6. Mohammadi J. Biochemical Disorders in Children with Febrile Seizure. Scientific Jour of Ilam Med University. 2008;16 (4):1–6. Namakin K, Shryfzadh G, Rezaei S. Demographic and clinical features febrile seizures. Journal of Birjand Medical Sciences 2010;17 (4):281–7. Rasoli M, Moghimian A. Causes of fever in children with febrile seizures in children’s hospital. Journal of Babol University of Medical Sciences. 1999;10 (3):131–7. Sadeghzadeh M, Asl P, Mousavi–Nasab N, kosha A, Pakdel M. Relationship between serum zinc levels and febrile seizure. Journal of Medical Science Zanjan. 2011;19 (74):17–24. Talebian A, Momtazmanesh N, Mousavi GH, Khojasteh M. Relationship between febrile seizure and anemia. Iran J Pediatr. Mar 2006;16 (1):79–86. Najaf–Zadeh A, Dubos F, Hue V, Pruvost I, Bennour A, Martinot A. Risk of bacterial meningitis in young children with a first seizure in the context of fever: a systematic review and meta–analysis. PLoS One. 2013;8 (1):1–8. Eseigbe E, Eseigbe P, Adama S. Febrile seizures in Kaduna, north western Nigeria. Niger Med J. 2012;53(3):140–4. Offringa M, Bossuyt PMM, Lubsen J, Ellenberg JH, Nelson KB, Knudsen FU, et al. Risk factors for seizure recurrence in children with febrile seizures: A pooled analysis of individual patient data from five studies. The Journal of Pediatrics. 1994;124 (4):574–84. Sampaio LP, Caboclo LO, Kuramoto K, Reche A, Yacubian EM, Manreza M. Prevalence of Epilepsy in Children From a Brazilian Area of High Deprivation. Pediatr Neurol. 2010 Feb;42 (2):111–7. van Zeijl JH, Mullaart RA, Borm GF, Galama JMD. Recurrence of febrile seizures in the respiratory season is associated with influenza A. The Journal of Pediatrics. 2004;145 (6):800–5. Berg A, Shinnar S, Hauser W, Leventhal J. Predictors of recurrent febrile seizures: a metaanalytic review. J pediater. 1990 Mar;116 (3):329–37. Berg AT. Risk of recurrence after a first unprovoked seizure. Epilepsia. 2008;49 (Suppl 1):13–8. Teach S, Geil P. Incidence of bacteremia, urinary tract infections, and unsuspected bacterial meningitis in children with febrile seizures. Pediatr Emerg Care. 1999;15 (1):9–12.